Symptoms and perceptions of risk factors among cancer patients attending a tertiary care hospital in Chandigarh, North India - Kumar, Dinesh; Goel, Naveen K.; Sharma, Munesh K.; Pandey, Awadhesh K. (International Journal Of Community Medicine And Public Health, 2021)
Background: With growing incidence of cancer, it is of prime interest to study views of cancer patients regarding their perceptions regarding cancer cure and its risk factors. The objective of the study was to explore opinions of cancer patients regarding the disease and perceived risk factors of various cancers. Methods: Results of present study are based on part of detailed findings of ICMR sponsored project wherein perceptions and beliefs of cancer patients were explored by interview method. Results: Study included 1117 new cancer patients including 501 (44.9%) males and 616 (55.1%) females representing different socio-economic classes. Spectrum of cases showed breast cancer (18.3%), head and neck cancer (10.2%) and cervical cancer (9.1%) as three major types of cancers. About 43% respondents were of the opinion that cancer can be curable and 15.0% thought it was due to displeasure of God. Symptoms of cancer perceived by them included mainly weakness and fatigue, loss of appetite and weight loss, indigestion or difficulty in swallowing as reported by 729 (65.3%), 568 (50.9%), 341 (30.5%) patients, respectively. Varied perceptions of patients regarding risk factors for different types of cancers were also reported. Conclusions: The study reported several misconceptions regarding cancer and risk factors perceived by cancer patients. There is an urgent need of health education to be made an integral part of cancer cure to avoid those misconceptions of patients prevent the disease and for better treatment outcomes. More in-depth studies are required to explore further opinions and to ascertain the findings.